Characterization of site location versus the causative fault in seismic demands of structures. (June 2022) - Monfaredi, Shakiba; Hamidi, Hamed; Khosravi, Horr
Abstract: This paper aimed at investigating the effect of site location versus the causative fault on the seismic demand of structures and addressing the related parameters from different aspects in order to possibly bridge the gap between structural engineering and engineering seismology. To this end, fundamental studies were carried out using different SDOF and 2DOF systems to obtain the imposed seismic demands in terms of spectral displacement (Sd ) contours, ductility demand contours (µ), Sdn /Sdp plots, and response resultant vectors. Both elastic and inelastic behavior regarding two ductility reduction factors (Rµ ) were incorporated. In order to correctly address the influence of geometrical and seismological parameters on structural seismic demands, a total number of 273 ground motions at different locations were generated using a recently developed technique to perform more than 30, 000 dynamic time-history analyses. In this regard, key parameters such as epicentral distance (R), angle (θ), slip distribution, rupture directivity, static offset, asperity location, pulse period (Tp ), and pulse amplitude (Ap ) were related to the structural responses and fully discussed. The results indicated that the vulnerability of structures could be rapidly and approximately assessed by elastic SDOF analyses or even by studying the ground motion characteristics such as pulse amplitude and pulse period. For low-period systems, the pulse amplitude ( Ap ) plays an important role, and for long-period systems, the pulse period ( Tp ) plays an important role. The relative rigidity of the structures vs. the pulse period plays a significant role in seismic demands. Finally, by getting far away from the epicenter, the Sdn /Sdp response ratio has been increased.